1987
DOI: 10.1063/1.98472
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in YBa2−xSrxCu3O7−δ

Abstract: Effect of silver solubility on microstructure and superconducting properties of YBa2Cu3−x Ag x O7−δ superconductors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1
2

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(41 citation statements)
references
References 5 publications
3
35
1
2
Order By: Relevance
“…For x = 0.50 it again decreases in agreement with earlier studies [2][3][4][5][6]. However, small impurity phases arises in x = 0.50 composition as increasing Sr content results in an unstable 123 phase.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…For x = 0.50 it again decreases in agreement with earlier studies [2][3][4][5][6]. However, small impurity phases arises in x = 0.50 composition as increasing Sr content results in an unstable 123 phase.…”
Section: Resultssupporting
confidence: 79%
“…According to Ona et.al [4] the O content decreases slightly in Sr doped samples due to structural disturbances. Along with decrease in O content, reduction in cell volume causes decrease in T c [2][3][4][5][6]. Veal et.al [5] accounted this T c reduction to local structure distortions occurred due to Sr doping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is illustrated in Fig. 7 system, the very first NPD study using a sample with y = 0.5 (z not given) concluded full ordering of the oxygen vacancies [33], but later Licci et al [24] revealed partial shift of the charge-reservoir oxygen from the b-axis site to the a-axis site due to Sr substitution. Thermoelectric power measurement has proven to be a powerful tool to reveal the metallicity of (fully-oxygenated) CuO chains in Cu-1212 and related copper oxides [36 -38].…”
Section: Resultsmentioning
confidence: 99%
“…One possible cause for this complex behavior is that the YBCO phase decomposes during preparations at ambient pressure when the Sr concentration exceeds a value of x ≈ 1 in the system YBa 2-x Sr x Cu 3 O 7-x [4]. At the grain boundary interface, it is possible that the Sr concentration is high enough for phase decomposition to occur, perhaps influenced by the level and kinetics of oxygenation.…”
Section: Effect Of Dopants On Grain Boundary Transportmentioning
confidence: 99%